Inflation-at-Risk in in the Middle East, North Africa, and Central Asia - Queyranne, Maximilien (IMF Working Papers; Working Paper ;, 2022)
This paper investigates inflation risks for 12 Middle East and Central Asia countries, with an equal share of commodities exporters and importers. The empirical strategy leverages the recent developments in the estimation of macroeconomic risks and uses a semi-parametric approach that balances well flexibility and robustness for density projections. The paper uncovers interesting features of inflation dynamics in the region, including the role of backward versus forward-looking drivers, non-linearities, and heterogeneous and delayed exchange rate pass-through. The results have important implications for the conduct of monetary policy and central bank communication in the Middle East and Central Asia and emerging markets in general.